内頸静脈血栓症を伴った咀嚼筋間隙膿瘍の1例 - 助川, 顕士; 外木, 守雄; 東郷, 拓也; 片倉, 朗; 西久保, 周一; 武安, 嘉大 (日本口腔外科学会雑誌, 2013)
In this super-aging society, treatment of patients with a variety of underlying diseases has become more complex. This case report describes a 78-year-old woman who was receiving long-term steroid therapy for rheumatoid arthritis. The patient was referred to our hospital for swelling of the right cheek and neck, associated with pain and trismus. Computed tomography (CT) revealed osteomyelitis of the mandible, which led to an abscess extending to the masticator space, facial cellulitis, and progressive internal jugular vein thrombosis. Clinical examination revealed decreased renal function and hypokalemia resulting from dehydration. We performed a surgical incision and drainage of the abscess to reduce inflammation. Steroid treatment, electrolyte abnormalities, and thrombosis were managed in coordination with a physician. Our experience shows that a multi-disciplinary team approach is required for the treatment of patients with underlying diseases.